2013
DOI: 10.1162/jocn_a_00410
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Reevaluation of Absolute Pitch: Behavioral and Electrophysiological Measurements

Abstract: Here, we reevaluated the "two-component" model of absolute pitch (AP) by combining behavioral and electrophysiological measurements. This specific model postulates that AP is driven by a perceptual encoding ability (i.e., pitch memory) plus an associative memory component (i.e., pitch labeling). To test these predictions, during EEG measurements, AP and non-AP (NAP) musicians were passively exposed to piano tones (first component of the model) and additionally instructed to judge whether combinations of tones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 91 publications
6
38
1
Order By: Relevance
“…By contrast, we propose that AP ability is more likely dependent on the second processing stage, namely the later cognitive process related to pitch labeling. Our results are further supported by a previous EEG study by Elmer et al (Elmer, Hänggi, et al, 2013;Elmer, Sollberger, et al, 2013), which also did not reveal any differences with respect to neurophysiological processes indicating early sensory processing between AP and NAP musicians during passive listening. Certainly, we are fully aware that other authors (Matsuda et al, 2013;Schulze et al, 2013;Wu et al, 2008;Itoh et al, 2005;Ohnishi et al, 2001;Hirata et al, 1999) found evidence for auditory processing differences as a function of AP ability.…”
Section: Mmn Responsessupporting
confidence: 91%
See 4 more Smart Citations
“…By contrast, we propose that AP ability is more likely dependent on the second processing stage, namely the later cognitive process related to pitch labeling. Our results are further supported by a previous EEG study by Elmer et al (Elmer, Hänggi, et al, 2013;Elmer, Sollberger, et al, 2013), which also did not reveal any differences with respect to neurophysiological processes indicating early sensory processing between AP and NAP musicians during passive listening. Certainly, we are fully aware that other authors (Matsuda et al, 2013;Schulze et al, 2013;Wu et al, 2008;Itoh et al, 2005;Ohnishi et al, 2001;Hirata et al, 1999) found evidence for auditory processing differences as a function of AP ability.…”
Section: Mmn Responsessupporting
confidence: 91%
“…This perspective is consistent with a large number of previous AP studies that adopted overt paradigms and reported reduced or even absent P300 amplitudes in AP participants (Crummer et al, 1994;Hantz et al, 1992;Wayman et al, 1992;Klein et al, 1984). Further evidence for the involvement of cognitive mechanisms in AP participants arises from labeling tasks, as manifested by a reduction in the P3b component, a reduction in the posterior positive and anterior negative slow waves (Itoh et al, 2005), or by increased N400 and LPC responses (Elmer, Sollberger, et al, 2013). Overall, the reduced P3a amplitudes in our study can be explained as decreased susceptibility among AP participants responding to tones, suggesting more efficient and parsimonious cognitive processing (Bendixen et al, 2010;Wetzel & Schröger, 2007;Wetzel, Widmann, Berti, & Schröger, 2006;Berti et al, 2004;Roeber, Berti, & Schröger, 2003;Gumenyuk et al, 2001;Escera, Alho, Winkler, & Näätänen, 1998;Schröger & Wolff, 1998).…”
Section: P3a Responsessupporting
confidence: 90%
See 3 more Smart Citations